Implementation of the ARCS Learning Model (Attention, Relevance, Confidence, Satisfaction) in Improving Student Learning Outcomes in Statistics Materials in Class X of SMAS Muhammadiyah Pamekasan - Yeni Apriliyanti; Septi Dariyatul Aini (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
This study employed a Classroom Action Research (CAR) design aimed at enhancing students’ learning outcomes in statistics through the implementation of the ARCS learning model in a tenth-grade class at SMAS Muhammadiyah Pamekasan. The research was carried out in two cycles. The first cycle focused on measures of central tendency, while the second cycle addressed measures of data position. The participants of this study were 24 tenth-grade students. Each cycle consisted of four stages: planning, action, observation, and reflection. The findings indicated that the implementation of the ARCS model had a positive effect on students’ learning outcomes. Students’ learning activities improved from an average score of 2,35 (fair category) in Cycle I to 3,13 (good category) in Cycle II. In addition, students’ responses to the learning process increased from an average of 67,5% (positive category) in Cycle I to 73,32% (positive category) in Cycle II. Furthermore, the level of classical learning completeness rose significantly from 20,83% in Cycle I to 70,83% in Cycle II. Based on these results, it can be concluded that the ARCS learning model is effective in improving students’ learning outcomes in statistics.